2016
DOI: 10.1016/j.jvs.2015.10.066
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of splanchnic artery aneurysms and outcomes after operative intervention

Abstract: Small SAAs (≤25 mm) are not prone to significant expansion and do not require frequent surveillance imaging. Imaging every 3 years for small SAAs is adequate. Aneurysms of the pancreaticoduodenal arcade and gastroduodenal aneurysms are more likely to rupture and therefore warrant a more aggressive interventional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 29 publications
1
71
0
4
Order By: Relevance
“…The intervention-based total morbidity rate of 10 % (8 % requiring treatment) for all interventions of the examined population showed good comparability with other studies (3 -8 %) [8,22,23]. The perioperative morbidity of conventional surgical therapy in terms of surgery-associated complications in a period of up to 30 days after the operation of 7 -13 % is also comparable [15,24,25]. The study by Hemp and Sabri showed that there is no significant difference between endovascular and surgical therapy regarding periprocedural morbidity and mortality but that there was a significant reduction in the length of the hospital stay after interventional therapy [10].…”
Section: Discussionsupporting
confidence: 61%
“…The intervention-based total morbidity rate of 10 % (8 % requiring treatment) for all interventions of the examined population showed good comparability with other studies (3 -8 %) [8,22,23]. The perioperative morbidity of conventional surgical therapy in terms of surgery-associated complications in a period of up to 30 days after the operation of 7 -13 % is also comparable [15,24,25]. The study by Hemp and Sabri showed that there is no significant difference between endovascular and surgical therapy regarding periprocedural morbidity and mortality but that there was a significant reduction in the length of the hospital stay after interventional therapy [10].…”
Section: Discussionsupporting
confidence: 61%
“…Bei einer interventionsbedingten Gesamtmorbidität von 10 % (8 % therapiebedürftig) im Rahmen aller Interventionen des untersuchten Kollektivs zeigt sich eine gute Vergleichbarkeit mit anderen Untersuchungen (3 -8 %) [9,22,23]. Die perioperative Morbidität der konventionellen chirurgischen Therapie im Sinne operationsassoziierter Komplikationen ist in einem Zeitraum von bis zu 30 Tagen nach der Operation mit 7 -13 % ebenfalls vergleichbar [15,24,25]. Die Übersichtsarbeit von Hemp u. Sabri hat gezeigt, dass es keinen signifikanten Unterschied zwischen endovaskulärer und chirurgischer Therapie bzgl.…”
Section: Komplikationsrateunclassified
“…92 % über im Mittel 36 Monate stabil waren (2-155 Monate!). Lediglich 5,8 % zeigten eine Ruptur [5].…”
Section: Behandlungsindikationunclassified
“…Insgesamt liegt die Morbiditätsrate periinterventionell zwischen 3 und 8 % [27][28][29]. Diese liegt damit unterhalb der publizierten Daten für die perioperative Morbidität offen chirurgischer Therapien von 7-13 % [5,21,30].…”
Section: Pro Endovaskuläre Therapieunclassified